Adubação da cultura da soja com torta de crambe - Schuroff, Caroline Koch (2018)
Due to a concern with renewable energy sources, there has been a search for alternatives to sustainable development with new perspectives and viability. Among these energy sources, biodiesel has received great attention. For the production of this fuel, oilseeds, such as soybeans, are used. However, in order not to compete with the food market, crambe seeds come as an option. During the process of extracting its oil, a by-product is generated, which is called cake. The objective of this work was to evaluate the fertilization of the soybean crop with crambe cake, in comparison to the mineral fertilization. The experiment was conducted at the Agronomic Institute of Paraná, in Santa Tereza do Oeste, state of Parana. Rates of 0, 2, 4 and 8 t ha-1 of crambe cake applied by broadcasting were evaluated, as well as an additional treatment with mineral fertilization. The experimental design was a randomized block design with four replications. The variables analyzed were productivity, plant height, thousand grain mass, lodging and nutrient contents in soil and foliar. The data were submitted to analysis of variance (ANOVA). The averages were compared with the use of Tukey test at 5 % probability. The crambe cake can be used to fertilize the soybean crop in soils with good fertility. In these cases, mineral fertilization can be substituted by crambe cake fertilization.